2018
DOI: 10.1002/joc.5880
|View full text |Cite
|
Sign up to set email alerts
|

Climatological representation of mesoscale convective systems in a dynamically downscaled climate simulation

Abstract: This research assesses the utility and validity of using simulated radar reflectivity to detect potential changes in linear and nonlinear mesoscale convective system (MCS) occurrence in the Midwest United States between the early and late 21st century using convection-permitting climate simulation output. These data include a control run and a pseudo-global warming (PGW) run that is based on RCP 8.5. First, using a novel segmentation, classification, and tracking procedure, MCS tracks are extracted from observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 52 publications
(101 reference statements)
1
32
0
Order By: Relevance
“…Fitzpatrick et al (2020) apply a similar method to outgoing longwave radiation fields coming from a CPM of 4.4 km resolution in order to track MCSs in the West African Sahel. Studies on MCSs in the Midwest US were also carried out by Haberlie and Ashley (2019) using a tracking method based on observed and simulated radar reflectivities.…”
Section: C1 Choice Of the Algorithmmentioning
confidence: 99%
“…Fitzpatrick et al (2020) apply a similar method to outgoing longwave radiation fields coming from a CPM of 4.4 km resolution in order to track MCSs in the West African Sahel. Studies on MCSs in the Midwest US were also carried out by Haberlie and Ashley (2019) using a tracking method based on observed and simulated radar reflectivities.…”
Section: C1 Choice Of the Algorithmmentioning
confidence: 99%
“…Therefore, it is reasonable to suspect that biased deep convective kinematic and/or microphysical properties may bias overall system evolution. Several recent studies show differences between observed and simulated MCS life cycles and geographical distribution over the U.S. Great Plains for seasonal and multiyear simulations using horizontal grid spacing of 3-4 km (Prein et al 2017c;Feng et al 2018;Haberlie and Ashley 2019;Scaff et al 2019). However, the ways in which underresolved deep convective drafts within MCSs impact mesoscale kinematic and microphysical evolution remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Weather radar data has been used for decades to identify CSM (e.g., Fujita, 1965). CSM identification can help assess the potential severity of an ongoing or imminent severe weather event (McNulty, 1995; Smith et al ., 2012), and can also be a useful tool for assessing operational (Snively and Gallus Jr., 2014) and climate model (Haberlie and Ashley, 2019) performance. The maturation of historical weather radar data archives has allowed the climatological exploration of radar‐derived event (e.g., thunderstorms, CSM ) frequency (Matyas, 2010; Fabry et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%